CHARACTERISTICS OF AGRICULTURAL INSURANCE: THE CASE OF COUNTRIES OF FORMER YUGOSLAVIA REGION - Petrović, Zdravko; Njegomir, Vladimir; Počuča, Sara (Economics of Agriculture, 2018)
Agricultural production is of great importance in the economies of region of former Yugoslavia, in relative terms significantly more than the global average. This production is carried out in the open air conditions and also is exposed to the effects of a large number of risks in relation to other activities. The research presented in this paper is the provision of agricultural insurance as a mechanism of risk management in the agricultural industry. The aim of the research is to show the key importance of this type of insurance and the determination of comparative differences in the effectiveness of its implementation in Serbia and other countries of the former common state in order to identify problems and propose potential solutions. The paper points out the importance and general characteristics of agriculture insurance and then to the common features of these types of insurance in all countries of the former Yugoslavia and then we analyze the effectiveness of this type of insurance in these countries. The results of the study are important for insurance companies in the region and may be useful to farmers and the state authorities concerned for a successful and sustainable agricultural production.